Impact of Torulaspora delbrueckii During Fermentation on Aromatic Profile of Vidal Blanc Icewine - Li, Jing; Hong, Mengnan; Qi, Baiyu (Frontiers in Microbiology, 2022)
Non-Saccharomyces yeasts usually have a positive effect on improving the diversity of wine aroma and increasing the differentiation of wine products. Among these non-Saccharomyces yeast species, Torulaspora delbrueckii is often studied and used in winemaking in recent years, but its application in icewine has not been reported yet. In this study, indigenous Torulaspora delbrueckii strains (TD1 and TD2) and Saccharomyces cerevisiae strains (commercial yeast SC1 and indigenous icewine yeast SC2) were sequentially inoculated for icewine fermentations; meanwhile, pure S. cerevisiae (SC1 and SC2) fermentations were used as the control; TD1, TD2 and SC2 strains used were screened from spontaneous fermentations of Vidal blanc icewine. The aim was to investigate the effect of T. delbrueckii on the aroma complexity of icewine, which is of great significance to the application of T. delbrueckii in icewine production. The results showed that T. delbrueckii was completely replaced by S. cerevisiae at the middle and later fermentative stages in mixed culture fermentations. Compared with the icewine fermented with pure S. cerevisiae, mixed culture fermented icewines contained lower acetic acid and ethanol, and higher glycerol. The inoculation of T. delbrueckii greatly impacted the levels of several important volatile compounds, and more 2-phenylethyl alcohol, isoamyl acetate, linalool, D-limonene, p-cymene and cineole were produced, and the fruity, flowery, and sweet characteristic was intensified. Moreover, the relevance of strain-specificity within T. delbrueckii to aroma compound differences was shown. To our knowledge, this study is the first to investigate the application of T. delbrueckii in Vidal blanc icewine fermentation, and volatile aroma compounds in the icewine fermented by T. delbrueckii and S. cerevisiae.